2009
DOI: 10.1111/j.1365-2427.2009.02184.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between environmental variables and groundwater biodiversity at the regional scale

Abstract: SUMMARY1. Relationships between the assemblage structure of stygobionts (i.e. obligate groundwater species) and habitat conditions in aquifers were explored in the French Jura based on 16 environmental variables and presence ⁄ absence data on stygobiotic species. The two data sets were simultaneously collected at a total of 269 sites. 2. The study aimed to (i) identify the environmental factors determining the composition of stygobiotic assemblages at the regional scale; (ii) define the ecological preferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 54 publications
10
54
0
Order By: Relevance
“…Humphreys 1999) and subsequent work in the Yilgarn has shown calcrete to be the most important habitat for stygofauna in that region (Humphreys 2001b;Cooper et al 2002). Projects such as PASCALIS in Europe have shown karst and alluvium to be the main stygofauna geologies (Dole-Olivier et al 2009) and, despite the survey results, it is likely that these are also the most productive geologies in most of the Pilbara.…”
Section: Factors Affecting Stygofauna Occurrencementioning
confidence: 93%
See 1 more Smart Citation
“…Humphreys 1999) and subsequent work in the Yilgarn has shown calcrete to be the most important habitat for stygofauna in that region (Humphreys 2001b;Cooper et al 2002). Projects such as PASCALIS in Europe have shown karst and alluvium to be the main stygofauna geologies (Dole-Olivier et al 2009) and, despite the survey results, it is likely that these are also the most productive geologies in most of the Pilbara.…”
Section: Factors Affecting Stygofauna Occurrencementioning
confidence: 93%
“…While this was considered to be largely a result of low sampling effi ciency resulting in ostracods not being collected from many sites where they actually occurred (see Eberhard et al 2009), several other studies have also found that water chemistry has little effect on stygofauna occurrence (e.g. Hahn 2006;Dole-Olivier et al 2009), despite the expectation that divalent cation and bicarbonate/ carbonate levels should be important for ostracods (Forester and Brouwers 1985;Gouramanis and De Deckker 2010) and perhaps other crustaceans (Glazier 1991). Little effect of water chemistry (other than salinity) was observed in the current analyses of the survey data.…”
Section: Factors Affecting Stygofauna Occurrencementioning
confidence: 99%
“…In the last decade, regional assessment of hypogean biodiversity using a hierarchical approach was carried out across Europe that also made a comparison of species richness between the vadose and phreatic zone of the same karstic aquifers possible (PASCALIS project;Dole-Olivier et al, 2009b;Galassi et al, 2009b;Stoch et al, 2009). At a regional scale, historical variables (glaciations and the age of geological formations), altitude and geology (pore size) primarily determined the hypogean community composition and species richness (Dole-Olivier et al, 2009a). A comparison of the vadose and phreatic zones revealed higher regional species richness in the former (Dole-Olivier et al, 2009b;Galassi et al, 2009b;Galassi et al, 2013), most probably due to higher habitat heterogeneity and habitat fragmentation.…”
Section: Study Sitementioning
confidence: 99%
“…Larvae of Chironomidae live in different habitats without selecting the available resources, minimising intraspecific and interspecific interactions (Dole-Olivier et al, 2009) so they are strongly influenced by variations in the physical and trophic microhabitats. The spatial segregation between different species in habitats can lead to spatial overlap, determining a trend for spatial intraspecific competitive interactions (Schmid-Arraya and Schmid, 1995).…”
Section: Introductionmentioning
confidence: 99%